Unusual Magnetic Field Responsive Circularly Polarized Luminescence Probes with Highly Emissive Chiral Europium(III) Complexes. Issue 2 (3rd November 2020) - Zhang, Junhui; Dai, Lixiong; Webster, Alexandra M.; Chan, Wesley Ting Kwok; Mackenzie, Lewis E.; Pal, Robert; Cobb, Steven L.; Law, Ga‐Lai
Abstract: Chirality is ubiquitous within biological systems where many of the roles and functions are still undetermined. Given this, there is a clear need to design and develop sensitive chiral optical probes that can function within a biological setting. Here we report the design and synthesis of magnetically responsive Circularly Polarized Luminescence (CPL) complexes displaying exceptional photophysical properties (quantum yield up to 31 % and |glum | up to 0.240) by introducing chiral substituents onto the macrocyclic scaffolds. Magnetic CPL responses are observed in these chiral Eu III complexes, promoting an exciting development to the field of magneto‐optics. The |glum | of the 5 D0 → 7 F1 transition increases by 20 % from 0.222 (0 T) to 0.266 (1.4 T) displaying a linear relationship between the Δglum and the magnetic field strength. These Eu III complexes with magnetic CPL responses, provides potential development to be used in CPL imaging applications due to improved sensitivity and resolution. Abstract : A series of chiral, water‐soluble, DO3A‐based Eu III complexes was designed and synthesized. The chiral substituents introduced onto the macrocyclic scaffolds enhanced the photophysical properties with quantum yields up to 31 % and |glum | up to 0.240. The |glum | value increased by 20 % from 0.222 to 0.267 under external magnetic field showing a linear response.